X-Ray Radiography of Alumina to Kovar Joining - Abdulhadi K.Jedran; Zareh A.Sarkiss; Selma M.Hussain (Engineering and Technology Journal, 2008)
In this work alumina samples were used to be joined with kovar alloy by usingdifferent filler types . Fillers were formed with different concentrations of Silver ,Copper , and Titanium powdered metals . These fillers where by mixing powdersand compacting by hydraulic press , and sintering by tube furnace with argonatmosphere of 1100 oC and time of 60 min. Alumina/Kovar assemblies were joinedin vacuum furnace of pressure of 2x10-4 torr at temperature of 850 oC and time of20 min. .X-ray radiography was used evaluates and detect the defect in contact areaThrtee types of defects were detected namely craqcks , voids and Non uniformity .Shear test was achieved to determine joint strength . Correlation between shear test(destructive test) and X- ray radiography (Non destructive test) was found .